Extensively drug-resistant typhoid fever; it’s not that simple: a case report - Rahim, Fawad; Amin, Said; Noor, Mohammad; Naeem, Malghalara; Bangash, Ayesha (Journal of the Pakistan Medical Association, 2023)
Multi-drug resistant strains of Salmonella typhi (S. typhi) has remained endemic in developing countries for the last two decades. With irrational use of antibiotics, an extensively drug-resistant (XDR) strain of S. typhi, sensitive only to Carbapenems and Azithromycin, has evolved which was first reported in Sindh, Pakistan, in 2018. Most of the cases of XDR S. typhi infection treated with antibiotics improve without any complications. Failure to respond to appropriate antibiotics should raise the suspicion of visceral abscesses. Splenic abscess is a rare complication of S. typhi infection. A patient with splenic abscess due to XDR S. typhi has been reported who responded to prolonged antibiotic treatment. We report the case of a young boy from Peshawar with multiple splenic abscesses due to XDR S. typhi which did not respond to percutaneous aspiration and culture-guided antibiotics for two weeks. ---Continue